STABILTAS KAROTENOID EKSTRAK PEWARNA BUAH PANDAN (Pandanus tectorius) PADA SUHU DAN pH AWAL PENYIMPANAN - Indriyani, Ni Made Dewi; Wartini, Ni Made; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 3 (2018): SeptemberDO - 10.24843/JRMA.2018.v06.i03.p04, 2018)
Pandanus fruit is a part of Pandanus tectorius plant that has a yellow to orange color. Pandanus fruit has the potential to be a natural source of yellow and orange dye. The dye obtained from pandanus fruit has unstable properties. The purpose of this study was to determine the effect of pH and temperature on the stability of carotenoids from pandanus fruit and to determine the pH and temperature that can maintain the stability of pandanus fruit extract during storage. The experiment of this study used Completely Randomized Design with two factors. The first factor was acidity (pH) that consisted of three levels: pH 4, 7, and 10. The second factor was temperature that consisted of two levels: 4±3ºC and 28±3ºC. The results showed that acidity (pH) had very significant effect (P<0.01) and temperature had significant effect (P<0.05) on carotenoids. The dye extract of pandanus fruit was more stable at the storage conditions of pH 7 (neutral) and cold temperature (4±3ºC) during 4 weeks storage with decreased of carotenoids was 34.29%. Keywords : Pandanus fruit extract, carotenoids, ph, temperature, stability